Effectiveness of Monocrystalline Solar Panel Tilt Angle to Output Power and Efficiency: Case study for Singaraja-Bali - Yasmini, Luh Putu Budi; Valentina, Diah Novita; Risha, Nurfa (Universitas Pendidikan Ganesha, 2025)
The tilt angle orientation influences the performance of solar panels. This study aims to determine the optimal tilt angle of solar panels, especially in the Singaraja area, which has the highest efficiency output power. This type of research is experimental research. The subjects involved in this study were monocrystalline solar panels tested at various tilt angles, namely 0°, 10°, 20°, 30°, 40°, 50°, and 60°. The data collection method was carried out by directly measuring the intensity of the incident sunlight and recording the output voltage and current values of the solar panel at each tilt angle variation. The data obtained was then analyzed to determine the output power and efficiency of the solar panel at each tilt angle by comparing the measurement results at various test times so that the tilt angle that produces the best performance under local environmental conditions can be identified. The results showed that the highest output power was obtained at 12:05 a.m. with a 10° tilt angle of 37.43 Watts. The lowest output power was obtained at 9:30 a.m. with a 60° tilt angle of 9.63 Watts. The highest efficiency is produced at an inclination angle of 10° by 11.62%. The lowest efficiency was obtained at a 60° tilt angle of 10.47%. The optimal tilt angle in Singaraja is 10° to produce high output power and good efficiency. Based on these findings, it can be concluded that the tilt angle of solar panels significantly influences the output power and efficiency of monocrystalline solar panels in the Singaraja region of Bali.